Modification of new built-up index to precisely extract and identify changes in the built-up area: a case study of Punjab State of India - Shaikh, Suraj; Paliwal, Rakesh; Patil, Abhijit; Panhalkar, Sachin; Palanisamy, Masilamani (Geodesy and Cartography, 2023)
Remote sensing is very useful for mapping and managing earth resources. The application of this technique has been widely used and proven useful in assessing temporal changes. The indices are used to distinguish different complex land covers, but there are still difficulties with distinguishing specific land covers. Therefore, the prime aim of this present investigation is to identify the changes in the built-up area using a modified new built-up index (MNBUI). The MNBUI is developed using the reference of four earlier developed indices. The built-up area of Punjab state is extracted from 2013 and 2017 year remote sensing satellite data using MNBUI. The result shows MNBUI is more accurate in terms of built-up area extraction as compared to the other two indices – New Built-up Index and built-up index models. The accuracy assessment is carried out to evaluate the accuracy of MNBUI with a random sampling technique. The mapping accuracy reported is 95% and 0.9333 in terms of overall accuracy (OA) and kappa coefficient (π) respectively.